A (dis)integrated stress response: Genetic diseases of eIF2α regulators. (31st August 2021) - English, Alyssa M.; Green, Katelyn M.; Moon, Stephanie L.
Abstract: The integrated stress response (ISR) is a conserved mechanism by which eukaryotic cells remodel gene expression to adapt to intrinsic and extrinsic stressors rapidly and reversibly. The ISR is initiated when stress‐activated protein kinases phosphorylate the major translation initiation factor eukaryotic translation initiation factor 2ɑ (eIF2ɑ), which globally suppresses translation initiation activity and permits the selective translation of stress‐induced genes including important transcription factors such as activating transcription factor 4 (ATF4). Translationally repressed messenger RNAs (mRNAs) and noncoding RNAs assemble into cytoplasmic RNA–protein granules and polyadenylated RNAs are concomitantly stabilized. Thus, regulated changes in mRNA translation, stability, and localization to RNA–protein granules contribute to the reprogramming of gene expression that defines the ISR. We discuss fundamental mechanisms of RNA regulation during the ISR and provide an overview of a growing class of genetic disorders associated with mutant alleles of key translation factors in the ISR pathway. This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein‐RNA Interactions: Functional Implications RNA in Disease and Development > RNA in Disease Translation > Translation Regulation RNA in Disease and Development > RNA in Development Abstract : Messenger RNA (mRNA) translation and decay are rapidly suppressed as RNA–protein granules form during the integrated stress response (ISR) to drive cell adaptation to stress conditions. Genetic diseases caused by mutant alleles of key ISR genes suggest an important role for the ISR in human development and health.